Daily life participation in PTSD: pilot study on patterns and correlators - Shapira, Ruth; Baris Ginat, Yisca Jessica; Lipskaya-Velikovsky, Lena (Frontiers in Psychiatry, 2024)
Participation in daily life activities with both the personal and community meaning is an important component of health and well-being. Even though there are mounting reports on the challenges in various aspects of daily-life functioning among individuals with post-traumatic stress disorder (PTSD), to date little research has been conducted on their comprehensive patterns of participation.The study aimed to describe objective and subjective participation dimensions in PTSD compared to healthy controls and investigate the association between personal and environmental factors and participation. Sixty-one individuals were enrolled in two groups: PTSD (N=31; age: M=34.3; women:77.4%) and healthy controls matched by age and gender. The PTSD group completed standard assessments for symptom severity, general cognition, executive function (EF), sensory processing, self-efficacy, functional capacity, and environmental properties. Both groups completed a participation questionnaire. Individuals with PTSD participated with low intensity and diversity, more occupations were abandoned (-4.73